EFFLEURAGE MASSAGE DAN METODE DEEP BACK MASSAGE DALAM MENURUNKAN SKALA NYERI MENSTRUASI - Ananda Putri, Efrina; Pratama, Kharisma; Ridlo Ronas, Mahin (Literasi Intelektual, 2025)
Background: According to the World Health Organization (2020), 90% of women experience menstrual pain, with 10–16% suffering severe pain. In Indonesia, the prevalence among adolescent girls reaches 64.24% (107,673 individuals). Although menstrual pain is not life-threatening, it can disrupt daily activities, cause fainting, depression, and reduce quality of life. Therefore, efforts to reduce menstrual pain are important. Objective: To determine the difference in the effectiveness of effleurage massage and deep back massage methods in reducing menstrual pain among SMAIT Almumtaz Pontianak students. Methods: This comparative analytical quantitative study used a quasi-experimental design with a two-group pre-test and post-test approach. A total of 32 respondents were selected using total sampling. Data were analyzed using the Marginal Homogeneity and Mann-Whitney tests. Results: The average decrease in menstrual pain frequency scores was 13.13 for the effleurage massage group and 19.88 for the deep back massage group. Both methods effectively reduced menstrual pain frequency. However, statistical analysis showed no significant difference in effectiveness between the two techniques, indicating that both are equally effective in reducing menstrual pain. Conclusion: Both effleurage and deep back massage are effective in lowering the frequency of menstrual pain. Nevertheless, based on the mean decrease, the deep back massage method appears to be slightly more effective than effleurage massage in alleviating menstrual pain among adolescent students.